The effective project manager competencies and skills for achieving success in projects in the UAE public sector - AL HAMMADI, FATIMA ABDULLA AHMED OMRAN (2021)
This study is aiming to contribute to the improvement of the PM performance in managing projects within the UAE public sector. The current leadership agenda, strategies and efforts have been dedicated to the development of project management performance, services, products of multiple vital public sectors in the UAE and increase the state reputation and income within the global countries. This was reflected in the increase of projects implemented and seen in all areas of daily life such as economy, construction, infrastructure, power and energy, education, health, and other essentials. However, because of lack of some project managers to new knowledge and skills for applying the discipline of project management effectively under the impact of rapid global changes and market competitiveness varied projects were ended with failure. This study was conducted to resolve such problem through increasing the understanding on the success and failure concept in the UAE public organizations, how this success has been measured, what are the factors perceived to support this success. Through using qualitative research method and conducting 15 interviews with senior managers and project managers in six organizations specialized in construction, IT, power and utilities and smart security. The participants were selected using convenience sampling type. Results and findings were generated through using Nvivo analysis software. The UAE public organizations were primarily depending on the adherence to the cost, time, and quality and scope which derived from the iron triangle notion for defining and measuring the success in projects. They also focusing on some other measures such as meeting the end-users needs and satisfying their stakeholders. While they perceived the engagement of stakeholders, the availability of resources and the project managers competencies and skills as main factors. In this regard, different competencies and skills were explored and considered to be most essentials for the achievement of success in the public projects. First of these was the competency of leadership which was at the top of the important competencies and skills, then the hard skills of the PM, then the communication, negotiation, adaptability, and lastly the emotional intelligence. Leaders and project management practitioners were recommended to increase their knowledge and soft abilities beside the hard ones through the training and workshops. They also ought to gain more understanding about the competency of the emotional intelligence and find more practices to apply it within their settings.